The connection between organizational structure variables and organizational justice views among correctional staff - Lambert, Eric G. (Journal of crime and justice, 2025)
A growing body of research on organizational justice views indicates that distributive (i.e. perceived fairness of outcomes) and procedural justice (i.e. perceived fairness of procedures to reach outcomes) are linked to salient correctional staff outcomes, such as job stress, job involvement, job satisfaction, organizational commitment, and life satisfaction; however, limited research investigates the relationships between workplace factors and the organizational justice views among prison staff. The current study investigated the relationships between organizational structure variables of instrumental communication, formalization, integration, and input into organizational decision-making with the procedural and distributive views of staff at a state-run U.S. prison. Data was from 257 staff who worked at a prison holding medium- and high-security convicted male offenders. Ordinary Least Squares (OLS) regression analysis indicated formalization, integration, and input were significantly positively correlated with procedural justice. Instrumental communication, however, was not significantly correlated with procedural justice. Input was a significant positive predictor of distributive justice, while instrumental communication, formalization, and integration were not significant predictors. Considerably more variance was explained in procedural justice compared to distributive justice views. The findings suggest that correctional administrators should be aware that input into decision-making is associated with prison staff’s views of both distributive and procedural justice.